2000
DOI: 10.1080/713774003
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculatory Dysfunction in Chronic Venous Insufficiency (CVI)

Abstract: The elevated ambulatory pressure in the peripheral venous system of chronic venous insufficiency (CVI) patients manifests itself not only in the form of disturbed macrocirculation but also and particularly in microangiopathic changes. For this reason, it is closely correlated with trophic disorders of the skin and can ultimately lead to ulceration. Using microcirculation research techniques, we are able to provide clear evidence of a typical microangiopathy in chronic venous insufficiency. Fifty CVI patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 11 publications
3
72
0
9
Order By: Relevance
“…The changes seen with capillaroscopy in the skin affected by venous insufficiency with dilated capillary loops also fit well with what we have described. 13 Retrograde resin venography has its limitations, not the least being that it is done in amputated limbs and is nonphysiological, bearing no relation to the hemodynamic subtleties of valve closure, blood flows, and pressure differ- ences that occur in vivo. In a retrograde resin cast, what lies behind competent valves is not seen, and unfortunately, the status of unfilled segments cannot be assumed with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…The changes seen with capillaroscopy in the skin affected by venous insufficiency with dilated capillary loops also fit well with what we have described. 13 Retrograde resin venography has its limitations, not the least being that it is done in amputated limbs and is nonphysiological, bearing no relation to the hemodynamic subtleties of valve closure, blood flows, and pressure differ- ences that occur in vivo. In a retrograde resin cast, what lies behind competent valves is not seen, and unfortunately, the status of unfilled segments cannot be assumed with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…23 which proved to be safe and effective in the above mentioned trial in elderly patients. 24 An important finding of this study was that the ginkgo preparation used was associated with a two-fold increase in the amount of insufficiency, 27 hypertension, insulin resistance, and sepsis, 28 and it is believed to play a role in metabolic syndrome, 29 Raynaud syndrome, 30 and erectile dysfunction. 31 Microcirculation is generally decreased in smokers, 32 and most likely also in patients with cognitive disorders.…”
Section: Efficacy and Safety Parametersmentioning
confidence: 94%
“…It is known that patients with CVI exhibit abnormalities of microcirculation, such as fewer capillaries and changes in capillary morphology, reduced oxygen concentration in the skin and greater capillary permeability to low molecular weight substances. 20 Another alternative hypothesis is that macrovascular changes are intermittent and are only present at the end of the day or at different points during the menstrual cycle. 21 Andreozzi et al studied of a group of these individuals using photoplethysmography and found that they had reduced calf muscle pump efficacy, suggesting that their symptoms may be caused by a reduction in the tone of vein walls, 22 since plethysmography parameters normalized when venous tone was increased artificially using elastic compression stockings, which are known to potentiate calf muscle pump (BMP) function.…”
Section: Discussionmentioning
confidence: 99%